الصنعة الفقهية من خلال منهجي منتقى الأخبار وشرحه نيل الأطار - بوعزة محمد; شريف حسين عمر; د/قبلي هني (جامعة عمار ثليجي الاغواط, 2023)
تناولت هذه الرسالة موضوع منهج الإمام الشوكاني في كتابه نيل الأوطار شرح منتقى الأخبار للمجد بن تيمية، وقد قُسم هذا البحث إلى فصلين وأربعة مباحث. الفصل الأول خاص بالجانب النظري وفيه نبذة مختصرة عن حياة الإمامين والتعريف بمؤلفيهما المنتقى في الأحكام الشرعية ونيل الأوطار. والفصل الثاني يظم الجانب التطبيقي للبحث وفيه مبحثين: الأول يظم جانب الصناعة الحديثية والآخر يضم الصناعة الفقهية وكتاب النكاح أنموذجا. وفي الختام توصلنا إلى نتائج تم إدراجه في الخاتمة. Summary This thesis dealt with the subject of Imam Al-Shawkani's methodology in his book "Nail Al-Awtar, Sharh Muntaqa Al-Akhbar" by Al-Majd Ibn Taymiyyah. This research was divided into two chapters and four investigations. The first chapter is concerned with the theoretical side, and it contains a brief overview of the life of the two imams, and an introduction to their selected authors in Shari’a rulings and Nayl al-Awtar. The second chapter organizes the applied side of the research, and it contains two sections: the first includes the modern industry aspect, and the other includes the jurisprudential industry and the book of marriage as a model. In conclusion, we reached results that were included in the conclusion